Is this London? Chance, crisis, aggression, weirdness and expense (Altre Modernità, 2018)
The article discusses a number of post-millennial London narratives in print and on screen. Significantly, these use chance as a structural device, contrive chance encounters between disparate characters and/or twists of fate in individual characters' lives. It is concerned with the changing fortunes of different areas of the metropolis by way of economic and cultural capital, migration within and beyond London, immigration and shifts in generic representations of the city. Chance here designates lucky, improbable, arbitrary and coincidental occurrences: modern inflections of a mythologised metropolitan theme.